System-of-Systems Thinking for Complexity and Innovation : A Study Based on the Trajectory of Systems Thinking - Chen, Qian ; 0000-0002-4264-6198; Chen, Jin; Magnusson, Mats; Xiao, Bin (Systems Research and Behavioral Science, 2025)
Complexity and innovation are emerging as fundamental issues for the future of human life and society. To deal with them, different versions of systems thinking have been proposed. However, System-of-Systems (SoS) thinking, based on the biperspectival principle and human reflexivity, has not yet been clearly recognized. The unclear distinction between ‘systems’ and ‘SoS’ thinking often results in confusion and misapplication of related concepts within the closed cycle of ‘system ↔ system-of-systems ↔ complex system ↔ system’, implying a need to address a set of inter-related questions: (1) What is the trajectory of systems thinking embracing complexity and innovation? (2) How does such a trajectory of systems thinking shape the future systems thinking in terms of SoS? and (3) What is SoS thinking? To address these questions, this article aims to explore the future of systems thinking in terms of SoS by embracing complexity and innovation, and delve into the theoretical origins of SoS theory, as well as its scientific connotation and logical framework. Firstly, the trajectory of systems thinking is outlined based on varying degrees of complexity across the dimensions known–unknown whole, and fixed–flexible relationships, respectively. Thereafter, the evolution path toward SoS thinking is analysed. Finally, the scientific connotation and logical framework of SoS thinking including (1) reshaping of boundaries, (2) governance of relationships, and (3) self-reflexivity and innovation, are explained based on the co-existence of paradoxes. The research results shed new light on the development of systems thinking in terms of SoS for complexity and innovation, by expanding the theories that integrate systems and complexity perspectives. Moreover, they provide practical guidance for applying SoS thinking based on the biperspectival principle and human reflexivity, along with a logical framework for engaging complexity and innovation at multiple levels of SoS.